The Inter-Regional Cooperation: the Impact on the Regional Economy (Khabarovsk Krai) - Anna Vasilyevna Belousova (Prostranstvennaâ Èkonomika, 2012)
The author obtains quantitative estimates (missing in official statistics) of the indicators of interregional interactions of the Khabarovsk Territory by the types of economic activities in the period of 2001–2010. The study shows that during the whole period of consideration three types of industries (the manufacture of coke, refined petroleum products and nuclear materials; the manufacture of food products, including beverages and tobacco; metallurgical production and production of finished metal products) assessed more than 90% of the volume of inter-regional export and more than 70% of the volume of inter-regional imports of the Khabarovsk Territory. On the basis of correlation-regression analysis of panel data from the processing industries of the Khabarovsk Territory the author receives the quantitative estimates of the output dependence on the volume of inter-regional exports and imports; defines the main directions of the inter-regional import products usage (final consumption, intermediate consumption, export) and proves the dominant role of the intra-regional factors and import transactions for the formation of the gross value added of the Khabarovsk Territory’s production